2015
DOI: 10.1117/12.2190737
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of z-axis linearity for arbitrary optical topography measuring instruments

Abstract: The calibration of the height axis of optical topography measurement instruments is essential for reliable topography measurements. A state of the art technology for the calibration of the linearity and amplification of the z-axis is the use of step height artefacts. However, a proper calibration requires numerous step heights at different positions within the measurement range. The procedure is extensive and uses artificial surface structures that are not related to real measurement tasks. Concerning these li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Previously, we showed that this allows for a similar calibration of the linearity z l and the amplification coefficient z α of the height axis [18,27]. Additionally, an integral calibration of the device based on the 3D roughness parameters is possible with the type AIR geometry [18]. The surface topography is based on an actual engineering surface and thus enables a practical calibration of multiple properties of surface topography measuring instruments.…”
Section: Design Of a "Universal Calibration Artefact" And Calibrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that this allows for a similar calibration of the linearity z l and the amplification coefficient z α of the height axis [18,27]. Additionally, an integral calibration of the device based on the 3D roughness parameters is possible with the type AIR geometry [18]. The surface topography is based on an actual engineering surface and thus enables a practical calibration of multiple properties of surface topography measuring instruments.…”
Section: Design Of a "Universal Calibration Artefact" And Calibrationmentioning
confidence: 99%
“…The surface topography is based on an actual engineering surface and thus enables a practical calibration of multiple properties of surface topography measuring instruments. The aforementioned linear Abbott-curve allows to achieve an almost stepless calibration of the height axis [18,27]. Additionally to specific linearity criteria that compare the n m ⋅ topography heights of the measured Abbott-curve ( ) C Mr with the target Abbott-curve, we use an alternative analysis to derive z α and z l , the parameters described in the ISO 25178-60x series [24].…”
Section: Design Of a "Universal Calibration Artefact" And Calibrationmentioning
confidence: 99%
See 3 more Smart Citations